Análise ergonômica da atividade na execução do serviço de revestimento de gesso - Almeida, Roberta Bibbó de (Universidade Federal de São Carlos, 2019)
The construction industry is an important segment of the Brazilian economy, generating a large volume of wealth and jobs for various sectors. Although over the years technological advances have occurred and many physical tasks have been replaced by mechanized and automated processes, due to the availability of construction workers at low costs most of the construction tasks are still performed manually. Work in the construction industry is among the most dangerous occupations, tasks often require excessive physical exertion or perform repetitive tasks over a long period of time, which can lead to health problems. In this context this research is inserted, through ergonomic analysis is intended to generate knowledge about the ergonomic risks that construction workers are exposed, more specifically those involved in the execution of wall and ceiling coating with plaster. To identify the ergonomic risks present the following tools were selected for the case studies: Rapid Entire Body Assessment (REBA), to analyze the postures adopted during the tasks; Occupational Repetitive Actions (OCRA); for analysis of repetitive tasks; and The standard metabolic equivalent (MET), to analyze the caloric expenditure in the activities. Through the experience with the workers, questionnaires and tools application, it was possible to understand the reality of these workers. Tool's application made possible to identify the criticality of the risks and also to identify in which stages of the production process they stand out. For the REBA tool, the tasks that showed greater criticality were the Receiving and Storage and the Coating of the lower part of the walls. The OCRA tool showed high exposure indexes in the analyzed activities, mainly for the right limb in the finishing activity on walls and ceilings. For the MET tool, the tasks that stood out with high caloric indexes were the Receiving and Storage and the Waste collection and storage.
Keywords: Análise ergonômica; Construção civil; Revestimento com gesso; Ergonomic analysis; Construction industry; Plaster coating; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL